The present and potential forest vegetation of the Ottawa, Ontario, region. - Billington, Clifford Charles. (University of Ottawa (Canada), 1978)
This study provides detailed descriptions of 149 stands of the least disturbed, most mature forest communities in the Ottawa, Ontario region. For each of these sampled communities, a complete summary is provided of tree population structure, coverage and constancy of all vascular understory species and habitat data including topographic position, drainage class, and soil characteristics. Six widespread and five locally-distributed forest alliances, comprising 21 forest associations, are defined and described on the basis of presently-dominant tree species. A dichotomous key to the associations is provided. The successional trends exhibited by the present associations are integrated into a flowchart based on tree population structures, tree ages and habitat characteristics. A discussion of succession and climax theory, terminology, variability within and between associations, environmental controls and disturbance factors is provided with emphasis on comparisons with previous investigations in eastern North America.
Keywords: Agriculture, Forestry and Wildlife.